The Correlation between Sociodemographic Characteristics and Chili Farmers' Knowledge on Pesticide Application in Tegal Regency - Maghfirah, Geubrina; Dadang, Dadang; Kumala Putri, Eka Intan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
Pest and disease are limiting factors in red chili cultivation. Chili farmers oftenuse synthetic pesticides to control pest and disease However, improper application of pesticide can cause deleterious effects to human and environment.The objective of research was to know the level of red chilli farmers understanding regardingpesticides use.This research was conducted in Bumijawa Subdistrict, Tegal District by interviewing farmers. A total number of 140 farmers werepurposely selected and divided into 4 groups, namely integrated pest management (IPM) monoculture,non IPM monoculture, IPM multiple cropping, and non IPM multiple cropping. Data analysis was performed using cross tabulation for likert scale questionnaire and Rank Spearman to analyze the relation among variables. Results showed that all four farmer groups had similar characteristics, i.e age range of 20-65 years, dominance ofelementary school graduates, and more than 10 years of farming experience. These group of farmers hadpositive score for application and safety principle of pesticide but they still had negative score on ecological aspect.Farmer’s age, level of education, and farming experience did not affect the knowledge of nonIPM monoculture and IPM monoculture groups. The level of education in non IPM multiple cropping group affected the application of pesticides. Farmer’s knowledge on pesticides usage and its safety application had significant correlation with farmer age and farming experience for IPM multiple cropping group.